2016
DOI: 10.31421/ijhs/22/1-2./1179
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pre-harvest spray of calcium nitrate, boric acid and zinc sulphate on yield and quality of Nagpur mandarin (Citrus reticulata Blanco)

Abstract: An investigation was conducted on uniform, healthy, eight year old trees of Nagpur mandarin (citrus reticulata Blanco) at Fruit Research Farm, Department of Fruit Science at College of Horticulture and Forestry, Jhalawar during 16 September, 2014 to 1 March, 2015. Various doses of calcium nitrate (1.0%, 2.0% and 3.0 %), boric acid (0.2 %, 0.4 % and 0.6 %) and zinc sulphate (0.2 %, 0.4 % and 0.6 %) were sprayed before harvesting and compared with untreated ones. The results obtained indicated that the trees spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 4 publications
2
1
0
Order By: Relevance
“…These findings closely align with earlier research by Gangle et al [18], which found that non-reducing sugars in guava fruits rose as storage time increased. Similar results were obtained by Meena et al [19] in Nagpur mandarin.…”
Section: Non-reducing Sugars (%)supporting
confidence: 91%
“…These findings closely align with earlier research by Gangle et al [18], which found that non-reducing sugars in guava fruits rose as storage time increased. Similar results were obtained by Meena et al [19] in Nagpur mandarin.…”
Section: Non-reducing Sugars (%)supporting
confidence: 91%
“…Thus, the cumulative effect of combination of Zn + Fe + B on faster cell division and cell expansion reflected on higher fruit volume. Similar results were also noted by Venu et al [11], Sawale et al [12], Deshlehra et al [13] and Rajamanickam et al [14] in acid lime, Tariq et al [21] in sweet orange, Meena et al [22] in Nagpur mandarin, Goswami et al [27], Jat and Kacha [28] and Bhoyar and Ramdevputra [26] in guava, Yadav et al [29] in pomegranate and Ambaliya and Masu [19] in aonla.…”
Section: Fruit Volume (Cc)supporting
confidence: 79%
“…The possible reason for increase in fruit weight by the micronutrients might be due to faster loading and mobilization of photo assimilates to fruit and involvement in cell division and cell expansion which ultimately reflected into more weight of fruit in treated plants [20]. These findings are supported by the results obtained by Venu et al [11], Sawale et al [12] and Rajamanickam et al [14] in acid lime, Tariq et al [21] in sweet orange, Meena et al [22] in Nagpur mandarin, Nehete et al [23] and Razzaq et al [17] in mango, Modi et al [24] in papaya, Ningavva et al [25] in banana, Bhoyar and Ramdevputra [26] in guava and Ambaliya and Masu [19] in aonla.…”
Section: Average Fruit Weight (G)mentioning
confidence: 55%
“… Leite et al (2011) and Bezerra et al (2023) found that calcium and boron are important nutrients in the stages of flowering, pollen germination, pollen tube growth, fruit set, and flower fertilization. Additionally, several studies have shown that the combined application of Ca + B promotes greater vegetative development, increased yield, fruit quality, and productivity in different crops compared to the isolated application of these elements ( Singh, Sharma & Tyagi, 2007 ; Bhatt et al, 2012 ; Meena et al, 2016 ; Hikal, Ibrahim & Abdelaziz, 2017 ; Meena et al, 2017 ; Al-Mayahi, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study clearly showed that spraying trees with calcium chloride and boric acid, either alone or combined, had a positive effect on yield parameters such as fruit set, fruit drop, fruit retention, overall tree yield, and fruit retention of Valencia orange trees compared to control. The increase in yield of Valencia orange fruits seen with the application of calcium and boron treatments may be due to the synergistic effect of boron and calcium nutrients, as they are both directly and indirectly involved in many physiological processes and enzyme activities ( Meena et al, 2016 ; Sheikh et al, 2021 ). The reduced fruit drop and increased fruit retention and fruit number recorded as a result of the effect of these treatments may be due to boron and calcium obstructing enzymes such as polygalacturonase from reaching their active sites, thereby retarding the occurrence of abscission zones ( Marcelis et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%